ショウワキチ シュウヘン ニ サンスル Evaporite ナラビニ オウショク エンルイ ノ コウブツ ソセイ - 兼島, 清; カネシマ, キヨ; 鳥居, 鉄也; トリイ, テツヤ; 宮平, 勝昭; ミヤヒラ, カツアキ; KANESHIMA, Kiyoshi; TORII, Tetsuya; MIYAHIRA, Katsuaki (国立極地研究所, 1968)
P(論文) During the summer mission of the 8th Japanese Antarctic Research Expedition (1966-1967), white evapontes and yellow salts were collected around Syowa Station, and their chemical and mmeralogical characteristics were studied. Eleven species of the white evapontes and eight species of the yellow salts were analyzed chemically, and mmeralogical components were identified by X-ray diffraction method. The white evapontes can be grouped into six types by the mmeralogical components as follows. (1) Halite, Sylvite, (L-1, L-2) (2) Halite, Sylvite, Bloedite (E-1, E-2, E-4) (3) Halite, Sylvite, Bloedite, Epsomite (E-5, E-13) (4) Halite, Sylvite, Bloedite, Thenardite (E-6, E-16) (5) Halite, Thenardite, Mirabihte, Bloedite, Gypsum (E-10, E-12) (6) Gypsum, Halite, Thenardite (E-15) The characteristics of the white evaporites found around Syowa Station are as follows. (1) Main component is halite. (2) Magnesium compounds are contained as epsomite or bloedite. (3) The presence of thenardite, mirabilite and gypsum is observed. (4) The white evapontes cannot be grouped by the mode of occurrence. The results of the X-ray diffraction analysis show that the yellow salts consist of gypsum, iron hydroxy sulf ate (carphosidente and copiapite), and halite. The yellow salts can be grouped into two types by the mineralogical components as follows (1) Gypsum, Garphosidente, Halite (E-8, E-14-B, E-9, E-14-A) (2) Gypsum, Carphosiderite, Copiapite Halite (E-7, E-14-G) To discuss the formation of yellow salts, samples of the soft yellowish brown weathered rock and hard quartzy rock were analyzed, and the dissolution experiments were also carried out. departmental bulletin paper